2008
DOI: 10.1002/rcs.182
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coracoacromial arch and rotator cuff analysed by a computer‐assisted method

Abstract: This preliminary results support the extension of the methodology to an in vivo protocol to be used during computer-assisted arthroscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In general, early in vitro studies concluded that the rotator cuff was closest to the coracoacromial arch between approximately 45 • ---90 • glenohumeral elevation. 27,28,30,46 Assuming a 2:1 scapulohumeral rhythm, 52 this range of glenohumeral elevation corresponds to approximately 68 • ---135 • of humerothoracic elevation. Consequently, these early findings supported the clinical theory that pain during mid-range may be due to subacromial rotator cuff compression.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In general, early in vitro studies concluded that the rotator cuff was closest to the coracoacromial arch between approximately 45 • ---90 • glenohumeral elevation. 27,28,30,46 Assuming a 2:1 scapulohumeral rhythm, 52 this range of glenohumeral elevation corresponds to approximately 68 • ---135 • of humerothoracic elevation. Consequently, these early findings supported the clinical theory that pain during mid-range may be due to subacromial rotator cuff compression.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…To investigate the feasibility of preserving the uterus for complete vaginal atresia, we increased the sample by literature searching. One hundred and one cases with complete vaginal atresia, who received cervicovaginal anastomosis or uterovaginal anastomosis, were identified from the literature 5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The outcomes of these patients are shown in Table 2.…”
Section: Feasibility Of Preserving the Uterusmentioning
confidence: 99%